2005
DOI: 10.1186/1743-8462-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy services to optimise the use of medications for mental illness: a systematic review

Abstract: The objective of this systematic review was to evaluate the impact of pharmacist delivered community-based services to optimise the use of medications for mental illness. Twenty-two controlled (randomised and non-randomised) studies of pharmacists' interventions in community and residential aged care settings identified in international scientific literature were included for review. Papers were assessed for study design, service recipient, country of origin, intervention type, number of participating pharmaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 61 publications
(56 reference statements)
1
41
0
Order By: Relevance
“…This critical narrative review revealed a positive effect of pharmacist interventions on antidepressant medication adherence by patients. The findings of this study are consistent with those of other researchers 34. In addition to revealing a positive effect of pharmacists’ intervention; this review also substantiated claims of improved medication adherence among depressed people who were treated by antidepressant medications prescribed by community mental health teams in Australia 34…”
Section: Discussionsupporting
confidence: 90%
“…This critical narrative review revealed a positive effect of pharmacist interventions on antidepressant medication adherence by patients. The findings of this study are consistent with those of other researchers 34. In addition to revealing a positive effect of pharmacists’ intervention; this review also substantiated claims of improved medication adherence among depressed people who were treated by antidepressant medications prescribed by community mental health teams in Australia 34…”
Section: Discussionsupporting
confidence: 90%
“…With the move towards deinstitutionalizing mental health care and encouraging management in the community setting, community pharmacists (CPs) can play a bigger role by providing pharmaceutical care (PC) services. A systematic review found that PC services by CPs resulted in improved adherence, and reduced the number of inappropriate medications prescribed in patients with mental disorders (Bell et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective chart review has indicated that duties performed by pharmacists in psychiatric settings can improve physician prescribing practices and enhance treatment outcomes [8]. These positive outcomes, associated with savings in drug acquisition costs could, theoretically, reduce the potential side effect burden of the psychotropic agents administered and could reduce the numbers of potentially inappropriate psychotropic medications prescribed for mental illness [9-11]. Pharmacists in the United Kingdom play a role at every stage of the patient's recovery, whether patients are being cared for in an acute setting or in the community.…”
Section: Introductionmentioning
confidence: 99%